Manufacturing method for steel parts
By controlling the steel composition and heat treatment process, carbides of specific particle sizes are formed, which solves the problem of insufficient wear resistance of steel under high-temperature friction conditions, and achieves excellent wear resistance under static and high-temperature conditions, which is suitable for specific mechanical components.
Patent Information
- Application Number
- JP2023102653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-18
- Filing Date
- 2023-06-22
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-06-10
AI Technical Summary
The prior art has shortcomings in improving the hardness and wear resistance of steel, especially under high-temperature friction conditions, which cannot meet the actual use needs of certain mechanical components.
By controlling the composition and heat treatment process in the steel, it is ensured that the steel contains a specific proportion of carbon, manganese, titanium, vanadium and other elements, and a carbide of a specific particle size is formed through hot rolling, cold rolling and heat treatment processes, forming a carbide containing at least one NB, TI, V to improve the wear resistance of the steel.
Under static and high-temperature friction conditions, steel exhibits excellent wear resistance and is suitable for applications such as fiber mechanical parts, bearing parts and mechanical tools that require high wear resistance.
Smart Images

Figure 0007626165000005 
Figure 0007626165000006 
Figure 0007626165000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel part, in particular to a steel part having excellent wear resistance, and also to a method for manufacturing said steel part. [Background technology]
[0002] Carbon steel, which is a steel with a high concentration of carbon, has high hardness and is therefore widely used as a material for steel parts that require wear resistance, such as textile machinery parts, bearing parts, and machine blades.
[0003] In the manufacture of general steel parts, cold-rolled steel sheets are processed into the shape of the parts, and then quenched and tempered. When hardness is increased by quenching, toughness decreases, but toughness can be improved by performing tempering after quenching. However, there is a problem in that the hardness decreases when tempering is performed.
[0004] Therefore, various techniques have been proposed to further increase the hardness of steel parts and achieve even better wear resistance.
[0005] For example, Patent Document 1 discloses a technology for improving formability and wear resistance in a steel plate having a ferrite-cementite structure by increasing the grain size of ferrite, spheroidizing carbides (mainly cementite) to an appropriate grain size, and reducing the pearlite structure.
[0006] Furthermore, Patent Document 2 discloses a technology in which cold-rolled steel sheet is annealed under specific conditions to change the metal structure to a pearlite structure, which is a lamellar structure of hard cementite and soft ferrite, thereby improving the wear resistance of the cold-rolled steel sheet.
[0007] Patent Document 3 discloses a technique for improving the wear resistance of steel plate by precipitating coarse Nb·Ti carbides having an equivalent circle diameter of 0.5 μm or more in the ferrite phase, which is the matrix structure.
[0008] Patent Document 4 discloses a technique for improving the wear resistance of steel materials by precipitating coarse carbides having a particle size of 2 μm or more in a matrix structure.
[0009] Patent Document 5 proposes a technology for improving the spheroidization rate of carbides such as cementite and improving toughness by subjecting a steel plate containing 0.5 to 0.7 mass% C to a finish annealing process immediately before final quenching and tempering.
[0010] Patent Document 6 proposes a technology for producing a soft high-carbon steel sheet with excellent punchability by performing an annealing finish at a stage immediately before the final hardening and tempering treatment, thereby increasing the number density of voids formed in the material.
[0011] Patent Document 7 proposes a technology for improving impact toughness and wear resistance in a high carbon steel plate by controlling the generation of cementite carbide, which does not contain niobium, titanium, or vanadium carbides, and adjusting the spheroidization rate and number density of the cementite carbide to desired values.
[0012] Patent Document 8 proposes a technology for improving toughness by adjusting the grain size of cementite carbide that does not contain niobium, titanium, or vanadium carbides, the grain size of retained austenite, and prior austenite through an annealing finish performed immediately before the final austempering heat treatment, and further by obtaining a bainite structure rather than a tempered martensite structure obtained through quenching and tempering, which is a typical thermal refining treatment. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] International Publication No. 2016 / 204288 [Patent Document 2] JP 2020-132953 A [Patent Document 4] JP 2017-190494 A [Patent Document 3] JP 2010-138453 A [Patent Document 5] JP 2009-24233 A [Patent Document 6] JP 2011-12316 A [Patent Document 7] Patent No. 6880245 [Patent Document 8] JP 2018-48374 A Summary of the Invention [Problem to be solved by the invention]
[0014] According to conventional techniques such as those proposed in Patent Documents 1 to 8, a certain degree of improvement in hardness and wear resistance of steel materials is observed. However, according to the study by the present inventors, it has been found that when steel parts manufactured using conventional steel materials as a material are actually used, sufficient wear resistance may not be obtained.
[0015] The present invention has been made in consideration of the above circumstances, and has an object to provide a steel part having excellent wear resistance. [Means for solving the problem]
[0016] The present inventors have investigated methods for solving the above problems and have come to the following findings.
[0017] (1) When steel parts are actually used, their temperature rises due to friction with other parts. For example, when a steel part is used as a textile machine part such as a knitting needle, the steel part is constantly exposed to friction with the textile, resulting in an increase in temperature.
[0018] (2) Therefore, in order to exhibit excellent wear resistance during actual use, it is necessary not only to suppress static wear caused by materials grinding against each other, but also to suppress the softening of the steel plate due to the rise in temperature caused by friction.
[0019] (3) In order to improve the wear resistance of steel parts, it is necessary to precipitate carbides containing at least one of Nb, Ti, and V in the steel. In this case, among the carbides, coarse carbides have the effect of suppressing static wear. For example, in the case of textile machine parts, the presence of coarse carbides can reduce the amount of wear caused by foreign matter such as fibers and pebbles attached to the fibers.
[0020] (4) On the other hand, fine carbides among the above carbides have the effect of suppressing the softening of the steel sheet due to the rise in temperature caused by friction. In other words, the presence of fine carbides suppresses the decrease in hardness caused by the recovery of dislocation structure when the temperature rises due to friction. In addition, in steel containing fine carbides, prior austenite grains are refined when quenched and tempered, which enhances the grain boundary strengthening effect, and as a result, the decrease in hardness caused by the recovery of dislocation structure is further suppressed.
[0021] (5) In order to obtain the above effects, it is necessary to control the average particle size of each of the coarse and fine carbides within a specific range.
[0022] The present invention has been completed based on the above findings, and the gist of the present invention is as follows.
[0023] 1. In mass percent, C: 0.6 to 1.25%, Si: 0.10-0.55%, Mn: 0.20-2.0%, P: 0.0005~0.05%, S: 0.01% or less, Al: 0.001 to 0.1%, N: 0.001 to 0.009%, Cr: 0.05 to 0.55%, and Contains one or more of Ti: 0.05-1.0%, Nb: 0.1-0.5%, and V: 0.01-1.0%, A steel slab having a composition with the balance being Fe and unavoidable impurities is heated under the conditions of a slab heating temperature of 1100°C or more and a holding time of 1.0 hour or more, The heated steel slab is hot-rolled under a finish rolling start temperature of 1010°C or higher to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cooled under the conditions of a time from the end of the hot rolling to the start of cooling: 2.0 seconds or less, an average cooling rate: 25 ° C. / s or more, and a cooling stop temperature: 640 ° C. to 720 ° C., The cooled hot-rolled steel sheet is coiled. The hot-rolled steel sheet after coiling is subjected to a first annealing under the conditions of an annealing temperature of 650°C or more and 720°C or less and an annealing time of 3 hours or more; The hot-rolled steel sheet after the first annealing is subjected to cold rolling at a rolling ratio of 15% or more and second annealing at an annealing temperature of 600 to 800 ° C. and a heating rate of 50 ° C. / h or more and 190 ° C. / h or less, which are repeated at least twice, and then subjected to final cold rolling at a rolling ratio of 30% or more to obtain a cold-rolled steel sheet; For the cold rolled steel sheet, Processing into part shape and The heat treatment includes quenching at a quenching temperature of 700°C to 950°C and a holding time of 1.0 minute to 60 minutes, and tempering at a tempering temperature of 100 to 400°C and a holding time of 20 minutes to 3 hours. The average grain size of prior austenite grains is 25 μm or less, Carbide containing at least one of Nb, Ti, and V; and The average particle size of the carbide particles having a particle size of 0.1 μm or more is 0.15 to 2.5 μm; The method for producing a steel part includes producing a steel part in which the average particle size of the carbide particles having a particle size of less than 0.1 μm is 0.005 to 0.05 μm.
[0024] 2. The composition of the components is, in mass%, Sb: 0.1% or less, Hf: 0.5% or less, REM: 0.1% or less, Cu: 0.5% or less, Ni: 3.0% or less, Sn: 0.5% or less, Mo: 1% or less Zr: 0.5% or less, B: 0.005% or less, and The method for producing a steel part according to 1 above, further comprising one or more selected from the group consisting of W: 0.01% or less.
[0025] The main configuration of another embodiment of the present invention is as follows.
[0026] 1. In mass percent, C: 0.6 to 1.25%, Si: 0.10-0.55%, Mn: 0.20-2.0%, P: 0.0005~0.05%, S: 0.01% or less, Al: 0.001 to 0.1%, N: 0.001 to 0.009%, Cr: 0.05 to 0.55%, and Contains one or more of Ti: 0.05-1.0%, Nb: 0.1-0.5%, and V: 0.01-1.0%, The balance is Fe and unavoidable impurities. The average grain size of prior austenite grains is 25 μm or less, Carbide containing at least one of Nb, Ti, and V; and The average particle size of the carbide particles having a particle size of 0.1 μm or more is 0.15 to 2.5 μm; The steel part has an average grain size of 0.005 to 0.05 μm among the carbides having a grain size of less than 0.1 μm.
[0027] 2. The composition of the components is, in mass%, Sb: 0.1% or less, Hf: 0.5% or less, REM: 0.1% or less, Cu: 0.5% or less, Ni: 3.0% or less, Sn: 0.5% or less, Mo: 1% or less Zr: 0.5% or less, B: 0.005% or less, and The steel part according to 1 above, further comprising one or more selected from the group consisting of W: 0.01% or less.
[0028] 3. The steel part according to 1 or 2 above, wherein the steel part is any one of a textile machine part, a bearing part, and a machine blade.
[0029] 4. A steel slab having the composition described in 1 or 2 above is heated under the conditions of a slab heating temperature of 1100°C or higher and a holding time of 1.0 hour or longer; The heated steel slab is made into a hot-rolled steel sheet under the condition of a finish rolling start temperature of Ac3 point or higher, The hot-rolled steel sheet is cooled under the conditions of a time from the end of the hot rolling to the start of cooling: 2.0 seconds or less, an average cooling rate: 25 ° C. / s or more, and a cooling stop temperature: 640 ° C. to 720 ° C., The cooled hot-rolled steel sheet is coiled. The hot-rolled steel sheet after coiling is subjected to a first annealing under the conditions of an annealing temperature of 650°C or more and 720°C or less and an annealing time of 3 hours or more; The hot-rolled steel sheet after the first annealing is subjected to cold rolling at a rolling ratio of 15% or more and second annealing at an annealing temperature of 600 to 800 ° C. and a heating rate of 50 ° C. / h or more, which are repeated at least twice, and then subjected to final cold rolling at a rolling ratio of 30% or more to obtain a cold-rolled steel sheet; For the cold rolled steel sheet, Processing into part shape and A manufacturing method for steel parts, comprising the steps of performing heat treatment including quenching at a quenching temperature of 750°C to 950°C and a holding time of 1.0 minute to 60 minutes, and tempering at a tempering temperature of 100 to 320°C and a holding time of 20 minutes to 3 hours. Effect of the Invention
[0030] According to the present invention, it is possible to provide a steel part having excellent wear resistance. The steel part of the present invention has excellent wear resistance not only under static conditions but also under conditions where the temperature is increased due to friction, and therefore can be suitably used for various applications including textile machine parts, bearing parts, and machine blades. [Brief description of the drawings]
[0031] [Figure 1] FIG. 2 is a schematic diagram showing the shape of a wear test piece. [Diagram 2] FIG. 1 is a schematic diagram of an abrasion test device. [Diagram 3] FIG. 2 is a schematic diagram showing the shape of an abrasion test device used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The present invention will be described in detail below. Note that the present invention is not limited to this embodiment. As described above, the present invention focuses on carbides containing at least one of Nb, Ti, and V. Therefore, in the following description, "carbides containing at least one of Nb, Ti, and V" may be simply referred to as "carbides".
[0033] [Component composition] The cold-rolled steel sheet of the present invention has the above-mentioned composition. The reasons for the limitations will be described below. In the following description, "%" as a unit of content refers to "mass%" unless otherwise specified.
[0034] C: 0.6 to 1.25% C is an element necessary for improving the hardness after quenching and tempering. In addition, C is also an element necessary for forming cementite and carbides with elements such as Nb, Ti, and V. In order to form the necessary carbides and obtain the hardness and wear resistance after quenching and tempering, the C content must be 0.6% or more. Therefore, the C content is 0.6% or more, preferably 0.7% or more. On the other hand, if the C content exceeds 1.25%, the hardness increases excessively and the material becomes embrittled. In addition, if the C content exceeds 1.25%, the surface scale becomes strong during heating, resulting in deterioration of the surface properties, and not only is it easy for cracks to appear on the surface during subsequent cold rolling, but cracks occur during quenching and wear resistance decreases. Therefore, the C content is 1.25% or less, preferably 1.20% or less.
[0035] Silicon: 0.10 to 0.55% Silicon is an element that has the effect of increasing strength through solid solution strengthening, and the increased strength also improves wear resistance. In order to obtain this effect, the Si content is set to 0.10% or more, preferably 0.12% or more. On the other hand, if the Si content is excessive, coarse ferrite is formed on the steel sheet surface during hot working, which inhibits the formation of carbides necessary for improving wear resistance in the subsequent process. Therefore, the Si content is set to 0.55% or less, preferably 0.50% or less, more preferably 0.45% or less.
[0036] Mn: 0.20~2.0% Mn is an element that has the effect of promoting quenching and suppressing temper softening, thereby improving hardness. In order to suppress temper softening, it is necessary to suppress the formation of C as cementite or to delay dislocation recovery, and Mn has both of these effects. Mn also has the effect of suppressing dislocation recovery due to frictional heat not only during tempering but also during use of steel parts. In order to obtain the above effect, the Mn content is set to 0.20% or more, preferably 0.25% or more. On the other hand, if the Mn content exceeds 2.0%, band-shaped structures are formed due to Mn segregation. In particular, abnormal grain growth and heterogeneity of the structure are likely to occur in the MnS segregation portion, which suppresses carbide formation and causes cracks and shape defects during part processing. Therefore, the Mn content is set to 2.0% or less, preferably 1.95% or less.
[0037] P: 0.0005~0.05% By adding a small amount of P, the hardness can be increased by solid solution strengthening, and as a result, the wear resistance can be improved. In order to obtain the above effect, the P content is set to 0.0005% or more, preferably 0.0008% or more. On the other hand, if the P content exceeds 0.05%, the strength of the grain boundary decreases and the material becomes embrittled. Therefore, the P content is set to 0.05% or less, preferably 0.045% or less.
[0038] S: 0.01% or less S forms sulfides with Mn and consumes Mn, which reduces hardenability. When hardenability is reduced, the strength of the steel is reduced, and as a result, the wear resistance is reduced. Therefore, the S content is set to 0.01% or less. On the other hand, from the viewpoint of improving wear resistance, the lower the S content, the better, so the lower limit of the S content is not particularly limited and may be 0%. However, excessive reduction leads to an increase in manufacturing costs, so from the viewpoint of industrial production, the S content is preferably set to 0.0005% or more, and more preferably set to 0.001% or more.
[0039] Al: 0.001 to 0.1% Al is an element necessary for deoxidation during steelmaking. Therefore, the Al content is set to 0.001% or more. On the other hand, excessive Al causes the formation of coarse nitrides. The nitrides are often formed on the surface of the steel, and the formation of cracks and voids originating from these nitrides is promoted, resulting in a decrease in wear resistance. Therefore, the Al content is set to 0.1% or less, preferably 0.08% or less, and more preferably 0.06% or less.
[0040] N: 0.001 to 0.009% By adding a small amount of N, fine nitrides are formed, and the grain size is refined to improve toughness. In order to obtain the above effect, the N content is set to 0.001% or more. On the other hand, if there is an excess of N, it bonds with Al to form coarse nitrides. The nitrides are often formed on the surface of the steel, and the formation of cracks and voids originating from these nitrides is promoted, thereby reducing wear resistance. Therefore, the N content is set to 0.009% or less, preferably 0.008% or less.
[0041] Cr: 0.05~0.55% Cr is an element that has the effect of increasing the hardenability and hardness of steel, and therefore adding Cr can improve wear resistance. To obtain the above effect, the Cr content is set to 0.05% or more, preferably 0.12% or more. On the other hand, if Cr is excessive, coarse Cr carbides and Cr nitrides are formed, and voids are generated around the Cr carbides and Cr nitrides, resulting in a decrease in the performance of the steel parts. In addition, the formation of Cr carbides prevents the formation of carbides that are effective in improving wear resistance. Therefore, the Cr content is set to 0.55% or less, preferably 0.95% or less.
[0042] The above-mentioned composition contains one or more selected from Ti: 0.05 to 1.0%, Nb: 0.1 to 0.5%, and V: 0.01 to 1.0%.
[0043] Ti: 0.05 to 1.0% Ti is an element that forms fine carbides and has the effect of suppressing both static wear and thermal wear. Ti also has the effect of improving wear resistance by making prior austenite grains fine during quenching and suppressing dislocation recovery. When Ti is added, in order to obtain the above effect, the Ti content is set to 0.05% or more, preferably 0.015% or more. On the other hand, if Ti is added in excess, the carbides become coarser than necessary, and the carbides become the starting points of voids and cracks, so that the workability when processing the steel plate into a part shape is reduced. Therefore, the Ti content is set to 1.0% or less, preferably 0.9% or less.
[0044] Nb: 0.1-0.5% Nb is an element that forms fine carbides and has the effect of suppressing both static wear and thermal wear. In addition, Nb also has the effect of improving wear resistance by making the prior austenite grains fine during quenching and suppressing dislocation recovery. When Nb is added, the Nb content is set to 0.1% or more in order to obtain the above effect. On the other hand, if Nb is added in excess, the carbides become coarser than necessary, and the carbides become the starting points of voids and cracks, so that the workability when processing the steel plate into a part shape is reduced. Therefore, the Nb content is set to 0.5% or less, preferably 0.45% or less.
[0045] V: 0.01 to 1.0% V is an element that forms fine carbides and has the effect of suppressing both static wear and thermal wear. V also has the effect of improving wear resistance by making prior austenite grains fine during quenching and suppressing dislocation recovery. When V is added, the V content is set to 0.01% or more in order to obtain the above effect. On the other hand, if V is added in excess, the carbides become coarser than necessary, and the carbides become the starting points of voids and cracks, so that the workability when processing the steel sheet into a part shape is reduced. Therefore, the V content is set to 1.0% or less, preferably 0.95% or less.
[0046] A cold-rolled steel sheet according to one embodiment of the present invention has a composition comprising the above-mentioned components with the balance being Fe and unavoidable impurities.
[0047] In another embodiment of the present invention, the above-mentioned composition may further contain one or more selected from the group consisting of Sb: 0.1% or less, Hf: 0.5% or less, REM: 0.1% or less, Cu: 0.5% or less, Ni: 3.0% or less, Sn: 0.5% or less, Mo: 1% or less, Zr: 0.5% or less, B: 0.005% or less, and W: 0.01% or less.
[0048] Sb: 0.1% or less Sb is an element effective in improving corrosion resistance, but if added in excess, it forms an Sb-rich layer under the scale formed during hot rolling, causing surface scuffs (scratches) on the steel sheet after hot rolling. Therefore, the Sb content is set to 0.1% or less. On the other hand, the lower limit of the Sb content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Sb content be 0.0003% or more.
[0049] Hf: 0.5% or less Hf is an element effective in improving corrosion resistance, but if added in excess, it forms a Hf-rich layer under the scale formed during hot rolling, causing surface scuffs (scratches) on the steel sheet after hot rolling. Therefore, the Hf content is set to 0.5% or less. On the other hand, the lower limit of the Hf content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Hf content be 0.001% or more.
[0050] REM: 0.1% or less REM (rare earth metal) is an element that improves the strength of steel. However, excessive addition of REM can delay the refinement of carbides and promote inhomogeneous deformation during cold working, which can deteriorate the surface properties. Therefore, the REM content is set to 0.1% or less. On the other hand, although there is no particular lower limit for the REM content, from the viewpoint of enhancing the effect of addition, it is preferable that the REM content be 0.005% or more.
[0051] Cu: 0.5% or less Cu is an effective element for improving corrosion resistance, but if added in excess, it will form a Cu-rich layer under the scale formed during hot rolling, causing surface scuffs (scratches) on the steel sheet after hot rolling. Therefore, the amount of Cu added is set to 0.5% or less. On the other hand, the lower limit of the Cu content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Cu content be 0.01% or more.
[0052] Ni: 3.0% or less Ni is an element that improves the strength of steel. However, excessive addition of Ni can promote inhomogeneous deformation during cold working and deteriorate the surface properties. Therefore, the Ni content is set to 3.0% or less. On the other hand, the lower limit of the Ni content is not particularly limited, but from the viewpoint of enhancing the effect of addition, the Ni content is preferably set to 0.01% or more.
[0053] Sn: 0.5% or less Sn is an effective element for improving corrosion resistance, but if added in excess, it forms a Sn-rich layer under the scale formed during hot rolling, which causes surface scuffs (scratches) on the steel sheet after hot rolling. Therefore, the Sn content is set to 0.5% or less. On the other hand, the lower limit of the Sn content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Sn content be 0.0001% or more.
[0054] Mo: 1% or less Mo is an element that improves the strength of steel. However, excessive addition of Mo can delay the spheroidization of carbides and promote inhomogeneous deformation during cold working, which can deteriorate the surface properties. Therefore, the Mo content is set to 1% or less. On the other hand, the lower limit of the Mo content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Mo content is set to 0.001% or more.
[0055] Zr: 0.5% or less Zr is an effective element for improving corrosion resistance, but if added in excess, it will form a Zn-rich layer under the scale formed during hot rolling, causing surface scuffs (scratches) on the steel sheet after hot rolling. Therefore, the Zr content is set to 0.5% or less. On the other hand, the lower limit of the Zr content is not particularly limited, but from the viewpoint of enhancing the effect of addition, it is preferable that the Zr content be 0.01% or more.
[0056] B: 0.005% or less B is an element that has the effect of improving hardenability and can be added as desired. However, if the B content exceeds 0.005%, cracks are likely to occur on the surface during hardening. Therefore, the B content is set to 0.005% or less. On the other hand, although there is no particular lower limit for the B content, from the viewpoint of enhancing the effect of addition, when B is added, the B content is preferably set to 0.0001% or more.
[0057] W: 0.01% or less W is an element that has the effect of improving hardenability and can be added as desired. However, if the W content exceeds 0.01%, cracks are likely to occur on the surface during hardening. Therefore, the W content is set to 0.01% or less. On the other hand, although there is no particular lower limit for the W content, from the viewpoint of enhancing the effect of addition, when W is added, the W content is preferably set to 0.001% or more.
[0058] Average grain size of prior austenite grains: 25μm or less By refining the prior austenite grains, the grain boundary strengthening effect is improved. As a result, dislocation recovery during frictional heat generation is suppressed, making it possible to maintain hardness even in a thermal environment and improving wear resistance. To achieve this effect, the average grain size of the prior austenite grains is set to 25 μm or less.
[0059] [carbide] The steel part of the present invention contains carbides containing at least one of Nb, Ti, and V. Conventionally, cementite has been used to improve wear resistance, but since carbides containing at least one of Nb, Ti, and V are harder than cementite, by precipitating carbides containing at least one of Nb, Ti, and V, it is possible to improve wear resistance more than conventionally.
[0060] In this case, as mentioned above, the coarse carbides have the effect of suppressing static wear, while the fine carbides have the effect of suppressing wear when the temperature is elevated due to friction. Therefore, by appropriately controlling the particle sizes of the coarse and fine carbides, it is possible to effectively improve the wear resistance of the steel part when it is actually used.
[0061] In the present invention, among carbides containing at least one of Nb, Ti, and V, those having a grain size of 0.1 μm or more are defined as coarse carbides, and those having a grain size of less than 0.1 μm are defined as fine carbides.
[0062] Coarse carbides Coarse carbides have the effect of suppressing static wear. For example, in the case of textile machine parts such as knitting needles, the presence of coarse carbides can reduce wear caused by rubbing against fibers or foreign objects such as pebbles attached to the fibers. However, if the average particle size of the coarse carbides is less than 0.15 μm, resistance to static wear is not exhibited. Therefore, the average particle size of the coarse carbides is set to 0.15 μm or more. On the other hand, if the carbides become too coarse, the opportunities for the carbides to function as resistance decrease, and the effect of resisting wear becomes saturated. Therefore, the average particle size of the coarse carbides is set to 2.5 μm or less. There are no particular limitations on the number density of the coarse carbides, but the higher the density, the better, and 250 pieces / mm 2 The coarse carbides may be present either at the grain boundaries or within the grains.
[0063] Fine carbide Fine carbides stabilize the dislocation structure and prevent dislocation recovery when the temperature rises due to frictional heat. Therefore, by precipitating fine carbides, softening due to frictional heat can be suppressed and wear resistance in a thermal environment can be improved. The effect of suppressing dislocation recovery increases as the average grain size of the fine carbides becomes smaller. Therefore, the average grain size of the fine carbides is set to 0.05 μm or less. On the other hand, if the carbides are excessively fine, the hardness increases excessively, leading to embrittlement. Therefore, the average grain size of the fine carbides is set to 0.005 μm or more. It is more effective for fine carbides to form within crystal grains than at grain boundaries. There are no particular limitations on the number density of the fine carbides, but the more the density, the greater the effect, and a density of 0.11 pieces / μm is the most preferable. 2 More preferably, it is equal to or greater than this.
[0064] The structure of the steel part of the present invention is not particularly limited, and the desired characteristics can be obtained as long as it satisfies the above conditions. Typically, the structure of the steel part of the present invention may be a structure consisting of tempered martensite, cementite, and carbides containing at least one of Nb, Ti, and V. The cementite and carbides containing at least one of Nb, Ti, and V are preferably spheroidized. Specifically, the spheroidization rate of the carbides, defined by the following formula using the average major axis La and the average minor axis Lb of the carbides, is preferably 0.71 or more. Spheroidization rate=Lb / La In addition, La is 100 μm 2 It can be calculated by dividing the sum of the major axes of all the carbides present in the range by the number of the carbides. 2 It can be calculated by dividing the sum of the minor axes of all the carbides present in the range by the number of the carbides.
[0065] Plate Thickness The thickness of the cold rolled steel sheet is not particularly limited and may be any thickness, but is preferably 0.1 mm or more, and more preferably 0.2 mm or more. The upper limit of the thickness is also not particularly limited, but is preferably 2.5 mm or less, more preferably 1.6 mm or less, and even more preferably 0.8 mm or less. When the thickness is 0.2 mm or more and 0.8 mm or less, it can be particularly suitably used as a material for knitting needles.
[0066] [Method of manufacturing cold-rolled steel sheets] Next, a method for producing a cold-rolled steel sheet according to an embodiment of the present invention will be described.
[0067] The cold-rolled steel sheet can be produced by sequentially carrying out the following steps on a steel slab having the above-mentioned composition. (1)Heating (2) Hot rolling (3) Cooling (4) Winding (5) First annealing (6) Cold rolling (7) Second annealing (8) Final cold rolling (9) Processing and heat treatment The above steps (6) and (7) are then repeated two or more times. Each step will now be described.
[0068] (1)Heating First, a steel slab having the above-mentioned composition is heated. The steel slab can be produced by any method without any particular limitation. For example, the composition of the steel slab may be adjusted by a blast furnace converter method or an electric furnace method. Moreover, casting of the molten steel into a slab may be performed by a continuous casting method or a blooming rolling method.
[0069] Slab heating temperature: 1100℃ or higher Retention time: 1.0 hours or more In the heating, the steel slab is heated under the conditions of a slab heating temperature of 1100°C or higher and a holding time of 1.0 hour or longer in order to homogenize the steel structure, dissolve some of the carbides contained in the steel, and precipitate the rest.
[0070] In the slab heating step, it is necessary to precipitate coarse Nb, Ti, V-based carbides bonded with a part of C, but other undissolved carbides are dissolved in the slab heating step in order to precipitate them to the desired dimensions in the later annealing step. If the slab heating temperature is lower than 1100°C, or if the holding time is shorter than 1 hour, coarse Nb, Ti, V-based carbides are not precipitated, and coarse Nb, Ti, V-based carbides for increasing the static wear resistance later cannot be obtained. On the other hand, if the slab heating temperature is too high, Nb, Ti, and V are dissolved and the amount of precipitation decreases, so it is preferable to set the slab heating temperature to 1380°C or less.
[0071] (2) Hot rolling The heated steel slab is then hot-rolled to produce a hot-rolled steel sheet. In the hot-rolling, rough rolling and finish rolling can be performed according to a conventional method.
[0072] Finish rolling start temperature: Ac3 point or higher If the finish rolling start temperature in the hot rolling is lower than Ac3 point, extended ferrite is generated in the hot rolled steel sheet, and this extended ferrite remains in the finally obtained cold rolled steel sheet. As a result, the generation of carbides in grains and grain boundaries, which are effective in improving wear resistance, is hindered. Therefore, the finish rolling start temperature in the hot rolling is set to Ac3 point or higher. On the other hand, the upper limit of the finish rolling entry temperature is not particularly limited, but it is preferably set to 1200°C or lower.
[0073] The Ac3 point (° C.) is calculated by the following formula (1). Ac3(℃) = 910 - (203 × C 1 / 2) + (44.7 × Si) - (30 × Mn) - (11 × Cr) + (400 × Ti) + (460 × Al) + (700 × P) +(104 × V) + 38 …(1) Here, the element symbols in the above formula (1) indicate the content (mass%) of each element, and are set to zero when the element is not contained.
[0074] (3) Cooling Time from the end of hot rolling to the start of cooling: 2.0 seconds or less Next, the hot-rolled steel sheet is cooled. At that time, if a long time passes between the end of hot rolling and the start of cooling, coarse ferrite grains are generated in the surface layer of the steel sheet and remain until the subsequent process. As a result, the precipitation of carbides in the grain boundaries and inside the grains, which is effective for improving wear resistance, is hindered. Therefore, the time from the end of hot rolling to the start of cooling is set to 2.0 seconds or less. On the other hand, from the above viewpoint, the shorter the time from the end of hot rolling to the start of cooling, the better, so the lower limit is not particularly limited. However, from the viewpoint of industrial production, it may be 0.5 seconds or more, or may be 0.8 seconds or more.
[0075] Average cooling rate: 25℃ / s or more Similarly, if the average cooling rate during the cooling is less than 25°C / s, coarse ferrite grains are generated in the surface layer of the steel sheet, and the precipitation of carbides, which is effective in improving wear resistance, is hindered. Therefore, the average cooling rate during the cooling is set to 25°C / s or more. On the other hand, although there is no particular upper limit to the average cooling rate, if the cooling rate is excessively high, the coiled shape becomes poor due to volume expansion caused by transformation during the subsequent coiling. Therefore, from the viewpoint of obtaining a good coiled shape, the average cooling rate is preferably set to 160°C / s or less, and more preferably set to 150°C / s or less.
[0076] Cooling stop temperature: 640℃~720℃ In addition, if the cooling end temperature during the cooling is too high, a non-uniform structure consisting of abnormally coarse and fine parts is formed, and as a result, the subsequent generation of carbides is hindered. Therefore, the cooling end temperature is set to 720°C or lower. On the other hand, if the cooling end temperature is too low, the coiled shape becomes poor due to volume expansion caused by transformation during coiling. As a result, non-uniform strain is introduced into the steel sheet in the subsequent cold rolling process, so that carbides of the desired grain size cannot be obtained, and the wear resistance is not improved. Therefore, the cooling end temperature is set to 640°C or higher.
[0077] (4) Winding After the cooling is stopped, the cooled hot-rolled steel sheet is wound into a coil shape. At this time, the coiling temperature is not particularly limited, but is preferably 600 to 700°C.
[0078] (5) First annealing Annealing temperature: 650℃ or higher, 720℃ or lower Annealing time: 3 hours or more The hot-rolled steel sheet after coiling is subjected to a first annealing under the conditions of an annealing temperature of 650°C or more and 720°C or less, and an annealing time of 3 hours or more. The structure of the hot-rolled steel sheet after coiling is a pearlite structure in which cementite and ferrite formed in a plate shape are arranged side by side. If the structure is pearlite, strain is not stably introduced in the subsequent cold rolling, and the cold-rolled steel sheet may have a defective shape. Therefore, it is necessary to break the pearlite structure and spheroidize the carbides. However, since the pearlite structure is stable against heat, it is easy to maintain the plate shape. It is necessary to hold the plate at a high temperature for a long time to divide the plate-shaped structure and increase the area of the interface. Therefore, the first annealing is performed at a temperature of at least 650°C or more for 3 hours or more. By further performing cold rolling and second annealing after the first annealing, the cementite in the plate shape is easily divided. On the other hand, if the annealing temperature is higher than 720°C, the structural change will proceed preferentially from one part, resulting in a mixed structure of coarse and fine structures, and ultimately, carbides of the desired size will not be obtained, and wear resistance will not be improved. There is no particular upper limit to the annealing time, but if it is too long, not only will the productivity decrease, but the effect will also saturate. Therefore, it is preferable to set it to 20 hours or less.
[0079] It is also preferable to subject the hot-rolled steel sheet to pickling prior to the first annealing.
[0080] (6) Cold rolling (7) Second annealing In cold rolling, the plate-shaped carbides that were broken down in the first annealing are further broken down and dispersed throughout the steel plate, and the second annealing process allows them to be dispersed throughout the plate at the desired dimensions, making this an important process for improving wear resistance. The plate-shaped carbides formed after hot rolling and coiling are stable, so they tend to remain for a long time, and the formation of plate-shaped carbides can cause voids and cracks. In addition, because they do not disperse throughout the steel plate, wear progresses unilaterally in the structure areas where carbides do not form.
[0081] Therefore, in order to precipitate carbides having a particle size effective for improving wear resistance, the hot-rolled steel sheet after the first annealing is subjected to cold rolling and second annealing at least twice. The plate-shaped carbides formed in the steel sheet are divided by cold rolling, and the carbides having the desired dimensions can be dispersed throughout the steel sheet by further performing the second annealing. In order to obtain the above effect, the rolling ratio of the cold rolling is set to 15% or more, and the annealing temperature in the second annealing is set to 600°C or more. On the other hand, if the annealing temperature is higher than 800°C, the prior austenite grains in the finally obtained structure become coarse, and the wear resistance when frictional heat is generated decreases. Therefore, the annealing temperature is set to 800°C or less.
[0082] In addition, if the heating rate in the second annealing is too slow, the carbides will become locally coarse, and fine carbides necessary for suppressing the softening of the steel sheet due to the temperature rise during friction will not be obtained. Therefore, the heating rate is set to 50° C. / h or more. On the other hand, the upper limit of the heating rate is not particularly limited, but it is preferably set to 200° C. / s or less.
[0083] The higher the reduction ratio in the cold rolling, the better, but if the reduction ratio is 65% or more, the shape of the obtained cold-rolled steel sheet may become unstable, so the reduction ratio is preferably less than 65%.
[0084] The cold rolling and the second annealing are repeated two or more times. By repeating the cold rolling and the annealing two or more times, the structure is refined and the carbides are dispersed throughout the steel sheet, and the desired carbide size can be finally obtained. In order to stably obtain a good steel sheet shape and thickness accuracy, it is preferable to repeat the number of times as many times as possible, and the upper limit of the number of times of repetition is not particularly limited. However, since the effect is saturated when the number of times of repetition exceeds five, it is preferable to set the number of times of repetition to five or less.
[0085] (8) Final cold rolling Rolling ratio: 30% or more After repeating the cold rolling and the second annealing two or more times as described above, final cold rolling is further performed at a rolling reduction of 30% or more. By performing final cold rolling at a rolling reduction of 30% or more, fine carbides are generated during final quenching and tempering, improving wear resistance when frictional heat is generated. Furthermore, by performing final cold rolling at a rolling reduction of 30% or more, the prior austenite grain size is refined, further improving wear resistance. A larger rolling reduction in the final cold rolling is better, but if it is 65% or more, the shape of the steel sheet may become unstable. Therefore, the rolling reduction is preferably less than 65%.
[0086] Furthermore, the finally obtained cold rolled steel sheet may be further subjected to an arbitrary surface treatment.
[0087] (9) Processing and heat treatment The cold-rolled steel sheet is then processed into a part shape and heat-treated to obtain a final steel part. The processing method is not particularly limited and can be any method. The processing may be, for example, at least one of punching, cutting, wire drawing, bending, and polishing.
[0088] The heat treatment includes quenching at a quenching temperature of 700° C. to 950° C. and for a holding time of 1.0 to 60 minutes, and tempering at a tempering temperature of 100 to 400° C. and for a holding time of 20 to 3 hours. The quenching and tempering conditions are important for controlling the grain size of carbides and the grain size of prior austenite to obtain excellent wear resistance.
[0089] To generate fine carbides, the quenching temperature (heating temperature during quenching) must be high. Therefore, the quenching temperature is set to 700°C or higher, preferably 720°C or higher. On the other hand, if the quenching temperature is too high, the prior austenite grain size becomes large and wear resistance decreases. Therefore, the quenching temperature is set to 950°C or lower, preferably 920°C or lower.
[0090] In order to generate carbides of the desired dimensions during the quenching, the heating temperature must be maintained for 1.0 minute or more. Therefore, the holding time is set to 1.0 minute or more. On the other hand, if the holding time exceeds 60 minutes, the prior austenite grains become coarse and the wear resistance decreases. Therefore, the holding time is set to 60 minutes or less. The cooling during the quenching is preferably performed to room temperature using oil or other cooling medium.
[0091] In order to improve hardness and obtain high wear resistance, it is necessary to lower the tempering temperature. Therefore, the tempering temperature is set to 400°C or less, preferably 380°C or less. On the other hand, if the tempering temperature is too low, fine carbides do not grow and the desired dimensions are not obtained. In addition, the hardness becomes too high and the material becomes brittle. Therefore, the tempering temperature is set to 100°C or more, preferably 130°C or more.
[0092] If the holding time during the tempering is less than 20 minutes, not only will the fine carbides not grow to the desired dimensions, but the hardness will become too high and embrittlement will occur, so the holding time is set to 20 minutes or more. On the other hand, if the holding time exceeds 3 hours, the fine carbides will become too coarse and will not reach the desired dimensions. Therefore, the holding time is set to 3 hours or less.
[0093] The heat treatment may be carried out after the processing or during the processing.
[0094] The above-mentioned method makes it possible to manufacture steel parts having excellent wear resistance. The steel parts can be used for any purpose without particular limitation, but are particularly suitable for use in applications requiring wear resistance, such as textile machine parts, bearing parts, and machine blades. EXAMPLES
[0095] Steel having the composition shown in Table 1 was melted in a converter and made into a steel slab by a continuous casting method. Next, the steel slab was successively subjected to heating, hot rolling, cooling, coiling, first annealing, cold rolling, second annealing, and final cold rolling to obtain a cold-rolled steel sheet with a final thickness of about 0.4 mm. Each process was carried out under the conditions shown in Tables 2 and 3, and cold rolling and second annealing were repeated the number of times shown in Table 3. Thereafter, the cold-rolled steel sheet was subjected to a heat treatment consisting of quenching and tempering under the conditions shown in Table 3 to obtain a sample. In this example, the processing process into a part shape was omitted.
[0096] The average grain size of the prior austenite grains, the average grain size of the coarse carbides, and the average grain size of the fine carbides in the obtained samples were measured by the following procedures.
[0097] (Prior austenite grain size) A test piece for carbide observation was taken from the obtained sample. The rolling direction cross section (L cross section) of the test piece for microstructural observation was polished, and then final polishing was performed with colloidal silica, and EBSD measurement was performed to identify the prior austenite grain boundaries. After identifying the prior austenite grain boundaries, the grain size and number of grains were obtained, and the circle equivalent diameter was calculated to obtain the average grain size. The evaluation results are shown in Table 4.
[0098] (coarse carbides) A test piece for carbide observation was taken from the obtained sample. After polishing the rolling direction cross section (L cross section) of the test piece for microstructure observation, the polished surface was corroded with 1 to 3 vol% nital solution to reveal the structure. Next, the surface of the test piece for microstructure observation was imaged at a magnification of 3000 times using an SEM to obtain a microstructure image. The particle size of each carbide containing at least one of Nb, Ti, and V contained in the obtained microstructure image was measured by a cut-off method, and the average value of the particle size of the carbides was calculated. Identification of Nb, Ti, and V-based carbides was performed using SEM-EDS analysis. Element mapping was performed on the observation field of view, and the cementite was separated from other carbides, and the other carbides were determined to be Nb, Ti, and V-based carbides. The evaluation results are shown in Table 4. Note that the items in which no coarse carbides were observed were left blank (-).
[0099] (fine carbide) A test piece for carbide observation was taken from the obtained sample, thinned to a thickness of about 70 μm, and then electrolytically polished to prepare an observation sample. The specimen was observed at 150,000 to 250,000 times with a TEM, and carbides containing at least one of Nb, Ti, and V were analyzed by TEM-EDS. The diameter of each carbide was obtained by a cut-off method, and the obtained particle diameters were arithmetically averaged to obtain the average particle diameter of the fine carbides. The evaluation results are shown in Table 4. Note that the items in which fine carbides were not observed were left blank (-).
[0100] (Wear resistance) The wear resistance of the resulting quenched and tempered steel sheets was evaluated under the following two conditions.
[0101] First, the wear resistance under static conditions, where almost no temperature rise due to friction occurs, was evaluated by the following procedure.
[0102] From each test piece, an abrasion test piece 10 having the shape shown in Fig. 1 was taken. Each abrasion test piece 10 had four holes 11 for threading the thread.
[0103] An abrasion test was carried out using the obtained abrasion test piece 10 and an abrasion tester 20 shown in Fig. 2. Specifically, the yarn S fed from the yarn unwinder 21 was run for 100,000 m per hole while in contact with the side of the hole 11 of the abrasion test piece 10, and the amount of abrasion was measured. A full-dull polyester knitting yarn was used as the running speed of the yarn S, and the running speed of the yarn S was set to 5 m / min. The tension of the yarn was adjusted to 10 ± 2 N / cm using a tension adjusting device 22.
[0104] As shown in Figure 3, a groove 12 is formed by wear at the location of the hole 11 that was in contact with the thread. Therefore, the thread was stopped when it had run 100,000 m, and the depth d of the groove 12 (wear depth) was measured with an optical microscope.
[0105] The same test was performed on four holes 11, and the average of the four obtained wear depths was regarded as the wear depth of the wear test piece. If the wear depth was less than 490 μm, the wear resistance was evaluated as good (◯), and if it was 490 μm or more, the wear resistance was evaluated as poor (×). The evaluation results are shown in Table 4.
[0106] Next, to evaluate the abrasion resistance under conditions involving a temperature rise due to friction, the test was carried out in the same manner as in the test under static conditions described above, except that the yarn running speed was set to 180 m / min, and the abrasion resistance was evaluated using the same criteria. The evaluation results are shown in Table 4.
[0107] [Table 1]
[0108] [Table 2]
[0109] [Table 3]
[0110] [Table 4] [Explanation of symbols]
[0111] 10 Wear test specimen 11 holes 12 grooves 20 Abrasion Testing Equipment 21 Thread unwinding device 22 Tension adjustment device 23 Thread winding device S thread d Wear depth
Claims
1. In mass percent, C: 0.6-1.25%, Si: 0.10 to 0.55%, Mn: 0.20-2.0%, P: 0.0005-0.05%, S: 0.01% or less, Al: 0.001-0.1%, N: 0.001 to 0.009%, Cr: 0.05 to 0.55%, and Contains one or more of Ti: 0.05-1.0%, Nb: 0.1-0.5%, and V: 0.01-1.0%, A steel slab having a composition with the balance being Fe and unavoidable impurities is heated under the conditions of a slab heating temperature of 1100° C. or more and a holding time of 1.0 hour or more; The heated steel slab is hot-rolled under a finish rolling start temperature of 1010°C or higher to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cooled under the conditions of a time from the end of the hot rolling to the start of cooling: 2.0 seconds or less, an average cooling rate: 25 ° C. / s or more, and a cooling stop temperature: 640 ° C. to 720 ° C., The cooled hot-rolled steel sheet is coiled. The coiled hot-rolled steel sheet is subjected to a first annealing under the conditions of an annealing temperature of 650° C. or more and 720° C. or less and an annealing time of 3 hours or more; The hot-rolled steel sheet after the first annealing is subjected to cold rolling at a rolling ratio of 15% or more and second annealing at an annealing temperature of 600 to 800° C. and a heating rate of 50° C. / h or more and 190° C. / h or less, which are repeated at least twice, and then subjected to final cold rolling at a rolling ratio of 30% or more to obtain a cold-rolled steel sheet; For the cold rolled steel sheet, Processing into part shape and The heat treatment includes quenching at a quenching temperature of 700°C to 950°C and a holding time of 1.0 minute to 60 minutes, and tempering at a tempering temperature of 100 to 400°C and a holding time of 20 minutes to 3 hours. The average grain size of prior austenite grains is 25 μm or less, Carbide containing at least one of Nb, Ti, and V; and The carbide particles having a particle size of 0.1 μm or more have an average particle size of 0.15 to 2.5 μm and a number density of 250 particles / mm 2 or more; The method for producing a steel part is such that the average particle size of the carbide particles having a particle size of less than 0.1 μm is 0.005 to 0.05 μm and the particle density is 0.11 particles / μm 2 or more.
2. The composition of the components is, in mass%, Sb: 0.1% or less, Hf: 0.5% or less, REM: 0.1% or less, Cu: 0.5% or less, Ni: 3.0% or less, Sn: 0.5% or less, Mo: 1% or less, Zr: 0.5% or less, B: 0.005% or less, and The method for producing a steel part according to claim 1, further comprising: W: 0.01% or less.
Citation Information
Patent Citations
High carbon steel sheet excellent in hardenability, fatigue property and toughness, and method for producing the same
JP2009024233A
Steel for wear resistant quenched-tempered component, and method for producing the same
JP2010138453A
Soft high-carbon steel sheet superior in punchability and method for manufacturing the same
JP2011012316A
Steel sheet for fiber machine component and manufacturing method therefor
JP2015190036A
Wear resistant steel sheet excellent in toughness
JP2017190494A